Diverse crops and input subsidies: a village-scale analysis in Mali. Issue 5 (3rd September 2022) - Assima, Amidou; Smale, Melinda; Kone, Bourema
ABSTRACT: An extensive literature assesses the productivity, farm income and fiscal impacts of agricultural input subsidy programmes reintroduced during the 2000s throughout Sub-Saharan Africa, as well as their fiscal sustainability, but less is known about how they affect cropping systems. We examine how fertilizer subsidies relate to one component of agricultural biodiversity – crop species diversity – by applying econometric models to nationally representative, village panel data in Mali. Total subsidized fertilizer received is strongly and negatively associated with crop richness, incentivizing the allocation of land to targeted crops away from other crops. These include cowpea, a neglected species which is grown as both a primary crop and intercrop and has agronomic, nutritional and income-generating benefits for farming families. The richer the crop species in a village, the more probable that cowpea is still grown. Findings are important for development policy in this agriculturally-dependent nation with numerous smallholders living below the poverty line.